2019
DOI: 10.1186/s12915-019-0710-0
|View full text |Cite
|
Sign up to set email alerts
|

Are we there yet? The long walk towards the development of efficient symbiotic associations between nitrogen-fixing bacteria and non-leguminous crops

Abstract: Nitrogen is an essential element of life, and nitrogen availability often limits crop yields. Since the Green Revolution, massive amounts of synthetic nitrogen fertilizers have been produced from atmospheric nitrogen and natural gas, threatening the sustainability of global food production and degrading the environment. There is a need for alternative means of bringing nitrogen to crops, and taking greater advantage of biological nitrogen fixation seems a logical option. Legumes are used in most cropping syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
93
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(114 citation statements)
references
References 216 publications
4
93
0
Order By: Relevance
“…EE including a single selection cycle also proved to be very useful in understanding the bacterial genetic bases of incompatible symbiotic interactions [47,166,167] and to analyze plant-mediated selection acting on rhizobial communities [168,169]. Complementary to synthetic biology and classical genetic approaches, EE will undoubtedly become an indispensable tool to select efficient, host-adapted microsymbionts in the perspective of optimizing current symbiotic associations or transferring N 2 -fixation in crops [170,171].…”
Section: Discussionmentioning
confidence: 99%
“…EE including a single selection cycle also proved to be very useful in understanding the bacterial genetic bases of incompatible symbiotic interactions [47,166,167] and to analyze plant-mediated selection acting on rhizobial communities [168,169]. Complementary to synthetic biology and classical genetic approaches, EE will undoubtedly become an indispensable tool to select efficient, host-adapted microsymbionts in the perspective of optimizing current symbiotic associations or transferring N 2 -fixation in crops [170,171].…”
Section: Discussionmentioning
confidence: 99%
“…Also, positive results in corn development and yield has been reported with Azospirillum brasilense inoculation (strains Ab-V5 and Ab-V6) under tropical conditions (Martins et al, 2018;Oliveira et al, 2018;Galindo et al, 2019b). However, greater responses with other PGPB can be achieved (Pankievicz et al, 2019). New research investigating Bacillus spp.…”
Section: Introductionmentioning
confidence: 99%
“…and Pseudomonas spp. as beneficial PGPB are being conducted, especially for annual crops (Oliveira et al, 2019;Pankievicz et al, 2019;Tavanti et al, 2020). For example, under tropical conditions, Bacillus subtilis inoculation (strains Pant001 and QST713) associated with Bradyrhizobium japonicum has been reported to increase soybean [Glycine max (L.) Merr.]…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, developing more e cient nitrogen-xing associations is of high importance given the pollution problems associated with the excessive use of chemical fertilizers (25,26). This requires a better understanding of the factors, including nutrient transport, in uencing the success of the symbiotic process (27)(28)(29). In line with this, it has been shown that every step in the establishment of Legumerhizobia symbioses is severely affected by B de ciency (30)(31)(32)(33)(34)(35).…”
Section: Introductionmentioning
confidence: 98%